Strategi Pengambilan Keputusan Terhadap Perluasan Layanan Bus Trans Jatim Ke Lamongan dan Bangkalan - Almy Aprilia Azizi Hasib; Denok Elvira Hanindiya; Adam Jamal (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The expansion of the East Java Trans Bus service to Lamongan and Bangkalan is a process of forming and setting a strategy for developing public transportation services that are safe, comfortable and affordable for the people of East Java. It is hoped that this expansion will make it easier for workers to obtain adequate transportation facilities and help the community to reach the economic and government center of Surabaya. Trans Jatim has been a mainstay of the community since its launch and is always in demand. With the expansion of the route to Lamongan and Bangkalan, it is hoped that it can provide much better public transportation services to meet the community's needs. The expansion of the East Java Trans Bus service to Lamongan and Bangkalan aims to determine the increase in public transportation services and also to determine the increase in Regional Original Income (PAD). This research uses the literature study method with the process of collecting data, journals, articles and information related to the topic under study. The presence of this service is expected to reduce road congestion, reduce pollution, reduce the number of accidents and reduce exhaust emissions. With the expansion of this service, it is hoped that it can become a milestone for efficient and sustainable transportation in East Java Province.